Heterobimetallic Pd‐Ru Catalysts for the Synthesis of Functionalized Polynorbornenes via Reductive Heck/ROMP Reactions - Cruz, Thais R. [UNESP]; Maia, Juliana I. P.; Maia, Pedro I. S.; Machado, Antonio E. H.; Goi, Beatriz E. [UNESP]; Delaude, Lionel; Carvalho‐Jr, Valdemiro P. [UNESP] (Wiley, 2025)
ABSTRACT Heterobimetallic complexes offer greater versatility for applications in homogeneous catalysis than their monometallic counterparts. To take advantage of this synergy, three [Pd( N,N,S ‐TSC)(4‐NH 2 Py)] complexes ( mono‐Pd Me , mono‐Pd Me,Me and mono‐Pd Ph ) were synthesized from [PdCl 2 (MeCN) 2 ] and appropriate thiosemicarbazide (TSC) ligand precursors, followed by the addition of 4‐aminopyridine (4‐NH 2 Py). The reaction of these mono‐Pd L complexes with [RuCl 2 (η 6 ‐ p ‐cymene)] 2 then afforded three heterobimetallic complexes with the generic formula [{RuCl 2 ( p ‐cymene)}‐μ‐{(4‐NH 2 Py)Pd (TSC)}] ( Ru‐Pd Me , Ru‐Pd Me,Me and Ru‐Pd Ph ). All these novel compounds were characterized by elemental analysis, spectroscopic techniques, cyclic voltammetry, and density functional theory (DFT) calculations. The molecular structure of mono‐Pd Me was determined by X‐ray diffraction analysis. The Ru‐Pd L complexes were evaluated as bifunctional catalysts in the reductive Heck coupling of norbornadiene (NBD) with iodobenzene and the ring‐opening metathesis polymerization (ROMP) of phenylnorbornene (Ph‐NBE). They were very active for the reductive Heck reaction, reaching yields higher than 90% when a [Pd]/[NBD]/[PhI] ratio of 1/418/1344 was employed at 120°C. Upon activation with ethyl diazoacetate (EDA), they were also able to polymerize Ph‐NBE with yields around 70% using a [Ph‐NBE]/[Ru‐Pd L ] ratio of 3000 at 50°C for 30 min. The Ru‐Pd Me,Me complex showed the highest activity in the ROMP of Ph‐NBE and was successfully applied for mediating the synthesis of poly (Ph‐NBE) from NBD via tandem catalysis.